Artificial light-harvesting supramolecular polymeric nanoparticles formed by pillar[5]arene-based host–guest interaction. Issue 9 (15th January 2018) - Sun, Cai-Li; Peng, Hui-Qing; Niu, Li-Ya; Chen, Yu-Zhe; Wu, Li-Zhu; Tung, Chen-Ho; Yang, Qing-Zheng
Abstract : Water-dispersible artificial light-harvesting supramolecular polymeric nanoparticles (LHSPNPs ) were prepared from bispillar[5]arene (bisP5A ) and anthracene-derived guest molecules (GD andGA ). Abstract : Artificial light-harvesting nanoparticles were prepared from supramolecular polymers comprised of pillar[5]arene with anthracene-derived donors and acceptors through host–guest interactions. The resulting water-dispersible nanoparticles displayed efficient energy transfer and excellent light harvesting ability in part because the steric bulk of pillar[5]arene suppressed the self-quenching of the chromophores.